Two homoclinic orbits for some second-order Hamiltonian systems - Cerda, Patricio; Faria, Luiz F.O.; Toon, Eduard; Ubilla, Pedro (Topological Methods in Nonlinear Analysis, 2019)
This paper is concerned with the existence of homoclinic orbits for a class of second order Hamiltonian systems considering a non-periodic potential and a weaker Ambrosetti-Rabinowitz condition. By considering an auxiliary problem, we show the existence of two different approximative sequences of periodic solutions, the first one of mountain pass type and the second one of local minima. We obtain two different homoclinic orbits by passing to the limit in such sequences. As a relevant application, we obtain another homoclinic solution for the Hamiltonian system studied in IJ.